SISTEM PENDUKUNG KEPUTUSAN PENERIMAAN BANTUAN PKH DENGAN METODE SIMPLE ADDITIVE WEIGHTING - Husaeni, Husaeni; Muslihudin, Muhamad; Aminudin, Aminudin (JMBI (Journal of Marketing and Business Intelligence), 2024)
The Family Hope Program (PKH) is a form of social assistance from the government that aims to improve the welfare of the poor. In the process of selecting PKH assistance recipients, obstacles are often encountered in determining prospective recipients who truly meet the established criteria. Therefore, a decision support system (DSS) is needed that can assist in making decisions objectively and accurately. This study proposes the use of the Simple Additive Weighting (SAW) method in a decision support system to determine PKH assistance recipients. The SAW method was chosen because of its ability to conduct multi-criteria assessments by giving weighting to each predetermined criterion. The selection process is carried out by determining the weight for each criterion, normalizing the data, and calculating the final preference value used to determine prospective recipients of assistance. The results of this study indicate that a decision support system based on the SAW method is able to provide more transparent, objective, and targeted selection results compared to conventional methods. With this system, it is hoped that the distribution of PKH assistance can be more effective and appropriate according to the economic conditions of the community in need.